1984
DOI: 10.1111/j.1540-4560.1984.tb00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Working at Home with Computers: Work and Nonwork Issues

Abstract: The term telecommuting refers to the substitution of telecommunications technology for physical travel to a central work location; it usually implies that the person is working in the home. This paper reviews organizational arrangements which allow employees to work at home on a regular basis as a substitute for attendance at the normal workplace. Two extreme cases of the implementation of such an arrangement are described. In the first, where the employee has a skill in demand and a job that is characterized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
0
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(166 citation statements)
references
References 6 publications
(4 reference statements)
4
157
0
5
Order By: Relevance
“…Implementation studies for example, [Alavi & Henderson 1981;Franz & Robey 1984;Ginzberg 1981;Lucas 1981;Markus 19831 [Bartol 1983;Baroudi 1985;Ivancevich et al 1983;Weiss 19831 are concerned with understanding the processes which result in job dissatisfaction, turnover, and stress for systems builders. Other researchers have focused on the power shifts generated by technology and technological dependence [Lucas 1984; Danziger et al 1982;Kling 1978Kling , 1980Kling & Iacono 1984;Laudon 1974;Olson & Primps 1984;Turner 1984;Zuboff 19881. These are only a sampling of topics that one can find under investigation yet all share a common thread.…”
Section: Consequences Of a Dominant Research Perspective In Behavioramentioning
confidence: 99%
“…Implementation studies for example, [Alavi & Henderson 1981;Franz & Robey 1984;Ginzberg 1981;Lucas 1981;Markus 19831 [Bartol 1983;Baroudi 1985;Ivancevich et al 1983;Weiss 19831 are concerned with understanding the processes which result in job dissatisfaction, turnover, and stress for systems builders. Other researchers have focused on the power shifts generated by technology and technological dependence [Lucas 1984; Danziger et al 1982;Kling 1978Kling , 1980Kling & Iacono 1984;Laudon 1974;Olson & Primps 1984;Turner 1984;Zuboff 19881. These are only a sampling of topics that one can find under investigation yet all share a common thread.…”
Section: Consequences Of a Dominant Research Perspective In Behavioramentioning
confidence: 99%
“…Much of the research on homeworking has found that homeworking is diversified by gender (Olson and Primps, 1984;Gurstein, 1991;Gunnarsson and Huws, 1997). 8 The indication from the current study is that because men define themselves primarily as wage earners, they have fewer personal conflicts when combining home and work than women.…”
Section: Personal Time and Spacementioning
confidence: 99%
“…There are potential difficulties and tensions that come with homeworking and teleworking (Bussing, 1998;Gurstein, 1991;Gurstein, 2001;Haddon, 1998;Huws, 1994;Moran, 1993). Homeworking can increase the permeability of the boundary between work and family domains, causing attempts to juggle work and family schedules to become more difficult (Bulos and Chaker, 1995;Olson and Primps, 1984;Crossen, 1990;Foegen, 1993;Gottlieb et al, 1998;Madigan et al, 1990;Royal College of Art, 1999;Sullivan, 2000).…”
mentioning
confidence: 99%
“…Ellison (1999) identifies "employees isolation," "boundaries between home and work," and "the impact of telework on the individual and the family," among others, as the major thematic concerns raised by telework research. As was the case with the emergence of teleworking, which altered the traditional approaches and policies concerning attendance, absenteeism, tardiness, and time off (Olson & Primps, 1984), mobile technology is redefining boundaries in the social and work contexts (Harmer & Pauleen, 2012). In the workplace, mobile technology affects various aspects of work and the workplace.…”
Section: Mobility and Work-life Balancementioning
confidence: 99%